Mutagenesis of the myogenin basic region identifies an ancient protein motif critical for activation of myogenesis. - Brennan, T J (1991)
Myogenin is a muscle-specific nuclear factor that acts as a genetic switch to activate myogenesis. Myogenin, MyoD, and a growing number of proteins implicated in transcriptional control share sequence homology within a basic region and an adjacent helix-loop-helix motif. Here we identify by site-directed mutagenesis a 12-amino acid subdomain of the myogenin basic region essential for binding of DNA and activation of myogenesis. The basic region of the widely expressed helix-loop-helix protein E12 is conserved at 8 of these 12 residues and can mediate DNA binding when placed in myogenin, but it cannot activate myogenesis. Replacement of each of the four nonconserved residues of the myogenin basic region with the corresponding residues of E12 reveals two adjacent amino acids (Ala86-Thr) that can impart muscle specificity to the basic region. These residues are specific to, and conserved in, the basic regions of all known myogenic helix-loop-helix proteins from Drosophila to man, suggesting that they constitute part of an ancient protein motif required for activation of the myogenic program.